PEMBAGIAN KEWENANGAN PEMERINTAH PUSAT-PEMERINTAH DAERAH DALAM OTONOMI SELUAS-LUASNYA MENURUT UUD 1945 - Abdul Rauf Alauddin Said (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
The concept of the relationship of authority between central and local governments within the unitary state of Indonesia in the context of the widest possible autonomy based on the Constitution of 1945. Whereas, the Republic of Indonesia as a state of law is based on constitutional system so that in every action of law concerning the concept of the relationship between central and local authorities should be established through legislation, whereas in juridical manner of authority is a right and legal authority of government. So, in the concept of the legal state (rechtstaat) all of government action that came from their authority should be based on legality principle. Therefore, the authority which is one form of power has legitimacy (validity), which will be the relationship that authority has a legitimate power. In the legislation related of the division of authority between central government and local government that regulated in Law Number 23 of 2014 on local government is clearly not reflect autonomy broad. Keywords:Authority, Local Government, Autonomy